Parental role conflict in night shift nursing workers: A perspective on feminist ethics towards nursing career development - Indrayani, Ni Luh Dwi; Kao, Chi-Yin (Innovation in Health for Society, 2024)
The source of professional nurses is inevitably needed in the near future. Contradictory, the nursing professional source remains debatable, as the fact of the occurrence of a nursing turnover rate. Studies reported personal reasons influenced the nurse turnover rate in which parental role conflict was included. The current study utilizes feminist ethics to explore parental role conflict in nurses, specifically in relation to their professional career development in nursing. Applying a feminist ethics approach to understanding parental role conflicts enables a comprehensive analysis of prospective alternatives from both policy and educational perspectives. Prospective alternatives grounded in feminist ethics can effectively address the moral imperatives of respecting nurses' career development preferences and general rights. This paper contributes to developing novel solutions for the ethical dilemmas of parental issues and night shifts in healthcare settings that could benefit healthcare professionals. Keywords: Feminist ethics; night shift nurses; nursing career development;parental role conflict; hospital